DETERMINATION OF DISCIPLINE, ORGANIZATIONAL CULTURE, AND COMPETENCE ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT IN THE REGIONAL REVENUE AGENCY OFFICE IN BATAM CITY - Syukror Rozi; Chablullah Wibisono; Nola Puspita Dewi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The Regional Revenue Agency (BAPENDA) of Batam City plays a strategic role in supporting regional revenue through tax and fee management. However, employee performance in recent years has shown a discrepancy between targets and actual results, influenced by various internal organizational factors such as discipline, organizational culture, competence, and employee commitment levels. This study aims to analyze the influence of discipline, organizational culture, and competence on employee performance through organizational commitment as a mediating variable. The study uses a quantitative approach with the Partial Least Square (PLS) method. The results show that discipline, organizational culture, and competence have a significant direct effect on performance and organizational commitment. Organizational commitment also has a significant effect on employee performance. The indirect influence of organizational culture and discipline on performance through commitment is insignificant, while competence has a significant influence through commitment. These findings emphasize the importance of improving competence and strengthening organizational commitment in supporting employee performance. The results of this study are expected to serve as a basis for the management of BAPENDA Kota Batam in formulating strategies to improve the quality of human resources to support more optimal public services.